THE APPLICATION OF TELEMATIC TECHNOLOGIES IN SLOVAKIA – THE POSSIBILITY OF IMPROVING ROAD SAFETY IN THE SLOVAK REPUBLIC - Ľubomír ČERNICKÝ; Alica KALAŠOVÁ (Scientific Journal of Silesian University of Technology. Series Transport)
Life on the road with all its aftermath and consequences works as a big triangle: driver-road-car. The main cause of road accidents is driver who can´t cope with increase of traffic density and with more and more powerful cars. Increasing number of new vehicles on our roads shows certain economic power of Slovakia and improving standard of living. The annual growth of more than seventy thousand new cars has as a result overcrowded Slovakian road network. Because of this, there is a special attention given to road traffic safety and its various factor at the present not only in our country, but also in the European Union. By joining the European Union we are committed to achieve standards in all areas that are comparable with European developed countries. In our paper we would analyze accident rate of traffic in recent years in Slovakia and design telematic measures to reduce it.